Program Milah (Mitra olah Sampah) Bank Sampah Sumber Mutiara sebagai Upaya Pemberdayaan Masyarakat dalam Pengelolaan Sampah di Kelurahan Sudimara Barat - Bima Aditya; Almisar Hamid (Lembaga Pengembangan Kinerja Dosen, 2025)
Environmental issues are one of the complex issues, starting from the state of the environment itself, social-society, to the problems that occur in the environment itself, the state of a dense environment raises problems, namely regarding the waste generated by the community. However, waste is not solely a problem, waste can be reduced in volume and used as an object that can benefit the community itself, one of which is through a community empowerment program through a waste bank, through a waste bank, the community participates in efforts to reduce waste which is expected to produce useful output. The focus of this research is related to the implementation of community empowerment through the waste processing partner program. Empowerment is carried out in several stages, from the awareness, understanding, utilization to the use stage, and involves elements of equality, independence, participation and sustainability. This research was conducted using a descriptive qualitative approach with data collected from interviews, observation, and documentation. The results of the study state that the waste management partner program as a community empowerment effort has succeeded in significantly empowering the community's ability and opportunity to take an active role in overcoming waste problems in their environment both in terms of economy, public awareness of waste reduction and the state of the environment itself.